Partial agonists of dopamine receptors: mechanisms and clinical effects of aripiprazole, brexpiprazole and cariprazine. (March 2023) - Cookson, John; Pimm, Jonathan
SUMMARY: Aripiprazole, brexpiprazole and cariprazine are partial dopamine (and serotonin) agonists developed as novel antipsychotics. This article discusses their pharmacology, evidence on their licensed and off-licence uses (including psychosis, mania, bipolar depression, Tourette syndrome and autism spectrum disorder) and side-effects. In schizophrenia, they have a low risk of Parkinsonism or hyperprolactinaemia, cause modest increases in body weight and are of moderate efficacy.